Syzygium humbertii and S. mortonianum spp. nov. (Myrtaceae) from Madagascar. (18th November 2015) - Byng, James W.
Abstract : Two new species, Syzygium humbertii Byng and S. mortonianum Byng, are described from Madagascar. When compared with other Madagascan Syzygium, S. humbertii Byng is characterised by sessile to subsessile leaves, orbicular to oval blades with usually cordate bases and rounded apices, and an obconic hypanthium. Syzygium mortonianum Byng is characterised by relatively long leaves that are typically wrinkled when dried, widely spaced venation, long petioles, and particularly dense capitate inflorescences with many flowers. Both new species are threatened with extinction and known from few contemporary collections.